Variability in NGC 3201 Giant Stars - Cortés, C. C. (2023)
We present the analysis of 510 light curves in V and I bands of 255 giant stars in the globular cluster NGC 3201.Our aim is to expand the sample of new types of variables reported in a previous study. These variables show ashort period (PV < 0.6 day) and a low amplitude (A(V ) < 0.06 mag.). We first searched for variability using thegeneralized Lomb?Scargle and phase dispersion minimization periodograms of the sample, discarding 167 stars asnon-variables. We then applied the significance test and reduced the sample to 88 giants, of which we classified 18as possible variables, 11 as dubious, 41 as non-variables, and 18 as variables. We finally determined the clustermembership of this sample and grouped each star based on their light-curve shape. The discovered variables showperiods in the range 0.2440 < PV < 0.5868 days and amplitudes between 0.010 < A(V ) < 0.064 mag. Within thesample of 18 variable stars, we report the discovery of an object with a period PV = 0.3603 ± 0.0012 and amplitudeA(V ) = 0.703 ± 0.029 mag that shows a RR Lyrae ab-type light curve. Additionally, we report two RR Lyrae aband c types with ultralow amplitude.